Republic of Armenia : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report, 2022)
The mission to Armenia took place between September 27-October 8, 2021 to assist the authorities to improve their Government Finance Statistics (GFS) compilation practices. The technical assistance (TA) mission was conducted by Ms. Ivana Jablonska and Mr. David Bailey at the request of the Ministry of Finance (MOF) and with the support of the IMF's Middle East and Central Asia Department (MCD). The main objectives of the mission were to assist the authorities in finalizing a comprehensive sectorized list of all public sector units -known as, the public sector institutional table (PSIT) - and in compiling annual general government GFS data for 2020.